The ecology of plant litter decomposition in stream ecosystems - Swan, Christopher M.; Boyero, Luz; Canhoto, Cristina (Cham, Switzerland Springer, 2021)
With almost 90% of terrestrial plant material entering the detrital pool, the processing of this significant carbon source is a critical ecosystem function to understand. Riverine ecosystems are estimated to receive, process and transport nearly 1.9 Pg of terrestrial carbon per year globally, highlighting the focus many freshwater ecologists have on the factors that explain decomposition rates of senesced plant material. Since Webster and Benfield offered the first comprehensive review of these factors in 1986, there has been an explosion of research addressing key questions about the ecological interactions at play. Ecologists have developed field and laboratory techniques, as well as created global scale collaborations to disentangle the many drivers involved in the decomposition process. This book encapsulates these 30+ years of research, describing the state of knowledge on the ecology of plant litter decomposition in stream ecosystems in 22 chapters written by internationally renowned experts on the subject.
The Ecology of Plant Litter Decomposition in Stream Ecosystems: An Overview -- Multi-scale Biophysical Factors Driving Plant Litter Dynamics in Streams -- Stoichiometry of Plant Litter Decomposition in Stream Ecosystems -- Global Patterns of Plant Litter Decomposition in Streams -- Plant Litter Decomposition in Intermittent Rivers and Ephemeral Streams -- Plant Litter Decomposition in Terrestrial Ecosystems Compared to Streams -- Biodiversity and Plant Litter Decomposition in Streams -- The Role of Key Plant Species on Litter Decomposition in Streams: Alder as Experimental Model -- Linking Microbial Decomposer Diversity to Plant Litter Decomposition and Associated Processes in Streams -- The Role of Macro Invertebrates on Plant Litter Decomposition in Streams -- The role of Microscopically Small Invertebrates in Plant Litter Decomposition in Streams -- Individual and Interacting Effects of Elevated CO2, Warming, and Hydrologic Intensification on Plant Litter Decomposition in Streams -- Causes and Consequences of Changes in Riparian Vegetation for Plant Litter Decomposition Throughout River Networks -- Effects of Exotic Tree Plantations on Plant Litter Decomposition in Streams -- Salt Modulates Plant Litter Decomposition in Stream Ecosystems -- Pathways, Mechanisms and Consequences of Nutrient-stimulated Plant Litter Decomposition in Streams -- How Toxicants Influence Plant Litter Decomposition in Streams -- Effects of Engineered Nanoparticles on Plant Litter Decomposition in Streams -- The Construction of Plant Litter Decomposition Curves -- Design and Analysis of Laboratory Experiments on Aquatic Plant Litter Decomposition -- Plant Litter Decomposition as a Tool for Stream Ecosystem Assessment -- Plant Litter Decomposition as a Contributor to Stream Ecosystem Service Provision.
Keywords: Stream ecology; Plant litter -- Biodegradation